INTEGRATION OF CELLULAR AUTOMATA - ARTIFICIAL NEURAL NETWORK TO PREDICT THE PATTERN OF LAND CHANGE INTO RESIDENTIAL FLOORS ON REMPANG ISLAND - Siregar, Razita Zahra; Anurogo, Wenang (Geographica: Science and Education Journal, 2025)
Unstable or fluctuating land use changes cause land degradation, reduced absorption capacity, and decreased land value. This study aims to predict land use on Rempang Island in 2029 using the Cellular Automata - Artificial Neural Network method to obtain a spatial picture of land use development, particularly residentials, so that the negative impacts of change can be anticipated early. CA is applied to simulate the spatial dynamics of land use change, and Artificial Neural Network is used to analyze historical data (land use in 2014, 2019, and 2024) and driving factors in predicting future land use changes. The driving factors used are slope inclination, area designation, and disaster risk. Land use change modeling was performed using the MOLUSCE plugin in QGIS software. The results of the study show that land use change in 2029 will experience a decrease in vegetation area of 5,987.15 hectares and open land area of 7,373.78 hectares. Residential and water areas are expected to increase. The residential area will increase to 1,932.32 hectares and the water area will increase to 170.55 hectares. The modeling of predicted land use on Rempang Island in 2029 produced an accuracy value with a strong interpretation of 79.01%.